The RNA binding proteins ZFP36L1 and ZFP36L2 are dysregulated in airway epithelium in human and a murine model of asthma - Rynne, Jennifer; Ortiz-Zapater, Elena; Bagley, Dustin C.; Zanin, Onofrio; Doherty, George; Kanabar, Varsha; Ward, Jon; Jackson, David J.; Parsons, Maddy; Rosenblatt, Jody; Adcock, Ian M.; Martinez-Nunez, Rocio T. (Frontiers in Cell and Developmental Biology, 2023)
Asthma is the most common chronic inflammatory disease of the airways. The airway epithelium is a key driver of the disease, and numerous studies have established genome-wide differences in mRNA expression between health and asthma. However, the underlying molecular mechanisms for such differences remain poorly understood. We investigated the expression and possible role of the tristetraprolin (TTP) family of RNA binding proteins (RBPs), which are poorly understood in asthma. The human TTP family is comprised of ZFP36, ZFP36L1 and ZFP36L2, and has essential roles in immune regulation by determining the stability and translation of myriad mRNAs encoding for inflammatory mediators. We found ZFP36L1 and ZFP36L2 mRNA levels significantly downregulated in the airway epithelium of patients with very severe asthma in different cohorts ( 5This is a provisional file, not the final typeset article healthy vs 8 severe asthma; 36 moderate asthma vs 37 severe asthma on inhaled steroids vs 26 severe asthma on oral corticoids). Integrating several datasets allowed us to infer that mRNAs potentially targeted by these RBPs are increased in severe asthma. Zfp36l1 was downregulated in the lung of a mouse model of asthma, and immunostaining of ex vivo lung slices with a dual antibody demonstrated that Zfp36l1/l2 nuclear localization was increased in the airway epithelium of an acute asthma mouse model, which was further enhanced in a chronic model. Immunostaining of human bronchial biopsies showed that airway epithelial cell staining of ZFP36L1 was decreased in severe asthma as compared with mild, while ZFP36L2 was upregulated. Restoring the levels of ZFP36L1 and ZFP36L2 in primary bronchial epithelial cells from patients with severe asthma decreased the mRNA expression of IL6, IL8 and CSF2. We propose that the dysregulation of ZFP36L1/L2 levels as well as their subcellular mislocalization contributes to changes in mRNA expression and cytoplasmic fate in asthma.